The Gantry as a Drive for a Horizontal Bike: Initial Investigation of Rotary Work - Łukasz Bereś; Paweł Pyrzanowski (Applied Bionics and Biomechanics)
The gantry drive (also, “the gantry”) is a mechanism that receives human-generated mechanical energy. The gantry used in a horizontal bike is a type of drive, and it is an alternative to a typical crankset. The purpose of this paper was to compare rotary work generated by the gantry and the crankset. The comparative criterion for the gantry and the crankset was work in rotational motion. The comparison was based on static tests; forces put into both drive systems were measured, and the rotary work was mathematically calculated. The forces put into the drive systems were measured for a man 177 cm tall and of 76 kg mass. To facilitate analysis and tests, the first gear wheel to receive force from the toothed rack (the gantry drive) was assumed to have the same radius as the crank (the crankset drive). Mathematical analysis performed for one full rotation (360°) of the first gear wheel and crankset showed that rotary work for the gantry was 2117.31 J and for the crankset 804.81 J. Ultimately, it was shown that the gantry can better receive mechanical energy from the human than the crankset. This means that a human will be less tired when riding a horizontal bike equipped with the gantry compared to a horizontal bike equipped with the crankset; assuming that in both cases, the bike speed is the same. Additionally, thanks to the use of the gantry drive in a horizontal bike, it is possible to achieve higher speeds compared to a horizontal bike equipped with the crankset.